PREVENTIVE ANTIARRYTHMIC PHARMACOTHERAPY OF FREQUENT ATRIAL FIBRILLATION PAROXYSMS AND SOME SUPRAVENTRICULAR TACHYCARDIA VARIANTS WITH PROPAFENONE AGAINST PLACEBO - Yu. A. Bunin; O. N. Denisov; L. F. Fedyakina (Российский кардиологический журнал)
.